A Concrete approach to abstract algebra - Sawyer, W. W. (New York Dover pub., 1959)
Brief, clear, and well written, this introduction to abstract algebra bridges the gap between the solid ground of traditional algebra and the abstract territory of modern algebra. The only prerequisite is high school-level algebra. Author W.W. Sawyer begins with a very basic viewpoint of abstract algebra, using simple arithmetic and elementary algebra. He then proceeds to arithmetic and polynomials, slowly progressing to more complex matters: finite arithmetic
Keywords: Algebra; Mathematics